VD_FINDINFO HC / 2015 / 226 vom 12. März 2015 - VD Tribunal cantonal (2015)
MESURE PROVISIONNELLE, DÉCISION SUR FRAIS, ASSISTANCE JUDICIAIRE | 105 CPP (CH), 241 al. 2 CPP (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)